2013
DOI: 10.3109/16066359.2013.838225
|View full text |Cite
|
Sign up to set email alerts
|

Injection drug users’ perceived barriers to using self-initiated harm reduction strategies

Abstract: Introduction and Aims Increasing the frequency with which injecting drug users (IDUs) engage in self-initiated harm reduction strategies could improve their health, but few investigations have examined IDUs’ perceived barriers to engaging in these behaviors. Method We interviewed 90 IDUs recruited from needle exchanges to assess: a) perceived obstacles to their use of two specific harm reduction strategies (i.e., test shots and pre-injection skin cleaning) designed to reduce two unhealthy outcomes (i.e., ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
3
11
0
1
Order By: Relevance
“…A large proportion of participants also reported craving, time constraints, inconvenience, lack of access to needles in places where one injects, and hassles from pharmacy staff when trying to purchase needles. Barriers in this study are similar to those found in other risk reduction barrier studies with PWID (e.g., Bonar & Rosenberg, 2014). As hypothesized, the data suggests that PWID who perceive greater barriers to both skin and needle cleaning actually engage in the behaviors less than those who report fewer barriers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A large proportion of participants also reported craving, time constraints, inconvenience, lack of access to needles in places where one injects, and hassles from pharmacy staff when trying to purchase needles. Barriers in this study are similar to those found in other risk reduction barrier studies with PWID (e.g., Bonar & Rosenberg, 2014). As hypothesized, the data suggests that PWID who perceive greater barriers to both skin and needle cleaning actually engage in the behaviors less than those who report fewer barriers.…”
Section: Discussionsupporting
confidence: 87%
“…Bonar and Rosenberg (2014) examined obstacles of two specific risk reduction practices – skin cleaning before injecting and using a test shot – and found that rushing to inject was the most commonly reported barrier for both risk reduction practices, while already purchasing drugs from a known dealer and lack of access to cleaning supplies were commonly reported barriers to doing a test shot and cleaning one’s skin (respectively). Additional barriers – including wanting to get high, being in withdrawal, and time pressures – were consistent with barriers reported in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…One survey of the self-efficacy of harm reduction practices, including tester shots, found that adherence to all harm reduction strategies surveyed was markedly lower when respondents were asked to imagine being in withdrawal [ 80 ]. A later study identified being in a hurry to use (24%) and purchasing drugs from a known dealer (20%) as the most significant barriers to the adoption of tester shots [ 81 ]. Health beliefs about perceived susceptibility to and severity of overdose may influence the adoption of overdose-related harm reduction methods such as tester shots [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…When examining the relationship between PWUD and people who sell drugs, PWUD often describe high levels of trust when buying from their "regular" drug seller [6,7], and consider a long and trusted relationship with the person selling them drugs as a source of protection against overdose [8][9][10]. PWUD frequently cite buying from a trusted or known drug seller as a harm reduction strategy that they engage in [8][9][10][11]; despite this, harm reduction programming and research has been slow to engage with people who sell drugs directly.…”
Section: Introductionmentioning
confidence: 99%